A STUDY TO ASSESS THE EFFECTIVENESS OF VIDEO ASSISTED TEACHING PROGRAM ON KNOWLEDGE REGARDING ACTIVATED CHARCOAL THERAPY FOR ORGANOPHOSPHATE COMPOUND POISONING PATIENTS AMONG IV YEAR B.SC. NURSING STUDENTS AT SELECTED COLLEGE IN KUMARAPALAYAM, NAMAKKAL DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Aim: The of this study was to assess the effectiveness of video assisted teaching program on knowledge regarding activated charcoal therapy for organophosphate poisoning patients among IV year B.Sc. nursing students.Methods: The Pre-experimental one group pre and post -test research design was selected for this study. A total of 50 IV year B.Sc. nursing students selected by using convenient sampling  technique. Assessment of the pretest level of knowledge regarding activated charcoal therapy for organophosphate compound poisoning patients among IV year B.Sc. nursing students by structured knowledge questionnaire. The interventions are video assisted teaching program regarding activated charcoal therapy for organophosphate compound poisoning. After the interventions, 7th day, the investigator conducted posttest level of knowledge regarding activated charcoal therapy for organophosphate compound poisoning patients by using the same structured knowledge questionnaire. The collected data were computerized and analyzed using SPSS version 25. The data was analyzed using descriptive statistics (distribution, mean, standard deviation) and inferential statistics (paired t test, and chi-square value test).Results: The result shows in pretest, majority of students 29 (58%) had inadequate knowledge and 21 (42%) had moderately adequate knowledge and in post- test, majority of students 47 (94%) had adequate knowledge and 3 (6%) had moderately adequate knowledge.Conclusion: The study concludes that video assisted teaching program was more effective on improving knowledge regarding activated charcoal therapy for organophosphate compound poisoning patients among IV year B.Sc. nursing students.